STRATEGI BERTAHAN HIDUP PENGENDARA MAXIM DI KECAMATAN BINA WIDYA KOTA PEKANBARU - Ari Suhadi; Indrawati " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2022)
Maxim was a plafrorm that provided service of transportation in the form of online motorcycle taxi in Pekanbaru City. Many types of transportation services, both online and offline available in Pekanbaru City caused Maxim riders to have difficulty finding passengers. The competition that occurs between these transportation services made it difficult for Maxim riders to meet their daily income. The Covid-19 pandemic was also one of the factors of difficulty in working as a Maxim riders. This study aims to find out how the survival strategy was carried out by the Maxim riders to be able to compete with its predecessor ojol platforms such as Grab and Go-Jek in working as a service that serves transportation in the form of online motorcycle taxis in order to meet their needs and what forms of innovation were carried out by the riders. Maxim riders during a pandemic so that they can still work normally and can still meet their income targets according to the needs of Maxim riders. The research data were collected through observation and documentation interview methods. Data analysis using qualitative descriptive analysis. From the results of the analysis in this study, it could be concluded that the Maxim riders used three survival strategies that are applied in their work to stay afloat. The survival strategies used were active strategies, passive strategies and network strategies to meet their needs in working as a Maxim riders. Keywords: Maxim Rider, Transportation Service, Online, Pandemic, Survival Strategy